Professores alfabetizadores da rede pública estadual e o Programa Letra e Vida - Castelhano, Valdete Júlio de Carvalho (2008)
The study intends to analyse the Languague and Life Program L&L contribution to the keep-learning practice from the Paulista Public State Teachers. Characterized as descriptive analytic of qualitative behavior, the research shows an individual interview as its main tool to the gather data. Theorically, the study has its foundations in three axis: firtstly, the reference explicative of the professional learning teaching as a long and continuos process for the whole life, secondly, it refers to a brief contextualization and to the literacy background in Brazil, serching documents from the Ministry of Education and documents from the teaching program as well to the background data. The last one is focused on the Languague and Life Program characterization. The gathered data reveals that learning to be a teacher and teaching is a long and complex process, in which, it blends personal and professional values. The Languague and Life Program proportionated a break into the interviewed teacher´s lives, changing their way of thinking. It also allowed them to accept new practices, but this time, intentional, conscious and overcoming in which could help their students to exceed their learning process and to become gradually independent and responsible for their studies. From the traditional methodology, in which the teacher teaches and the students learn, the teachers became their students partners, building up together the learning process, pointing out new meanings and presenting problematics that make sense and can awake the pleasure of learning.